Incorporation of dietary palm date pits in all-male Nile tilapia (Oreochromis niloticus) diets - NEDAL MOHAMMED SIDDIG SWAR; ASAAD HASSAN WIDAA MOHAMED (Smujo International, 2018)
Swar NMS, Mohamed AHW. 2018. Incorporation of dietary palm date seeds in all-male Nile tilapia (Oreochromis niloticus) diets. Nusantara Bioscience 10: 193-202. The study utilizes a 45-days randomized factorial design 3×2, three levels (25, 50 and 75%) of palm date seeds, three levels (non, with and without) of 3% bakery yeast (Saccharomyces cerevisiae) and three replicates. The observation was carried out in twenty-one plastic aquaria. All-male Nile tilapia (Oreochromis niloticus) fingerlings were put in each aquarium. Each aquarium was provided with well-aerated and triggered dechlorinated tap water with an average weight of 1.9±1.11 g/fish (10 fish/aquaria) and a total length of 5.18±0.69 cm/fish. Fish were given food three times/day (10 days, at 8.30,11.30, 3.30 A.M) at a rate of 12, 8 and 4% of body weight, to examine the impact of partial substitution of animal protein (fish meal) in the diet on growth achievement, carcass contexture, feed utilization, condition factor (k) and feed expense. Seven experimental diets were prepared; control diet (T0, CP 36.84) concluding 45% (fish meal) as animal protein and 0% (palm date seed meal) plant protein. Tested diets (T1, T2 and T3) concluding 25, 50, 75% with 3% bakery yeast (CP 35.71, 35.53, 34.74) and 25, 50, 75% without yeast (CP36.01, 36.27 and 35.57) respectively ; so, they substitute about 75, 50, and 25 of fish meal diet respectively. The outcomes showed that, tilapia were given food on T1, T2 and T4 diets (25, 50, and 25%) substitution with and without yeast respectively registered the greater growth achievement, feed and protein utilization than other experimental diets such as control diet, also they indicate the highest condition factor (K) grades which state that the fish are in decent health. Tilapia were given food by diet T3 (25% fish meal) T5, T6 (50 and 25% fish meal) with and without yeast respectively possessed deficient growth and diverged remarkably (p>0.05) from the other diets. Diet contexture remarkably had an impact on carcass contexture. These data prompted that Palm date seed with and without yeast S. cerevisiae can, to a certain extent, substitute fish meal (animal protein) in a diet for all-male Nile tilapia fingerlings at level-up to 50 and 25% with and without yeast respectively, without any unfavorable result on accretion achievement. Furthermore, fish diet, partially substituted with 3% yeast, resulted from superior accretion achievement than other diets within the present experimental circumstance. This study showed that there is an economic efficiency of confounding palm date seed (plant protein) as partial substitution of fish meal (animal protein) with and without yeast in all-male Nile tilapia, that it could decrease the expense of feeds.